Ex Vivo Antioxidant Activity of Selected Medicinal Plants against Fenton Reaction-Mediated Oxidation of Biological Lipid Substrates - Namratha Pai Kotebagilu; Vanitha Reddy Palvai; Asna Urooj (Biochemistry Research International)
Free radical-mediated oxidation is often linked to various degenerative diseases. Biological substrates with lipids as major components are susceptible to oxygen-derived lipid peroxidation due to their composition. Lipid peroxide products act as biomarkers in evaluating the antioxidant potential of various plants and functional foods. The study focused on evaluation of the antioxidant potential of two extracts (methanol and 80% methanol) of four medicinal plants, Andrographis paniculata, Costus speciosus, Canthium parviflorum, and Abrus precatorius, against Fenton reaction-mediated oxidation of three biological lipid substrates; cholesterol, low-density lipoprotein, and brain homogenate. The antioxidant activity of the extracts was measured by thiobarbituric acid reactive substances method. Also, the correlation between the polyphenol, flavonoid content, and the antioxidant activity in biological substrates was analyzed. Results indicated highest antioxidant potential by 80% methanol extract of Canthium parviflorum (97.55%), methanol extract of Andrographis paniculata (72.15%), and methanol extract of Canthium parviflorum (49.55%) in cholesterol, low-density lipoprotein, and brain, respectively. The polyphenol and flavonoid contents of methanol extract of Andrographis paniculata in cholesterol (r=0.816) and low-density lipoprotein (r=0.948) and Costus speciosus in brain (r=0.977, polyphenols, and r=0.949, flavonoids) correlated well with the antioxidant activity. The findings prove the antioxidant potential of the selected medicinal plants against Fenton reaction in biological lipid substrates.